2019
DOI: 10.1016/j.biopsych.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Incentives Boost Model-Based Control Across a Range of Severity on Several Psychiatric Constructs

Abstract: Our results demonstrate that model-based control can reliably be improved independent of construct severity for most measures. This suggests that incentives may be a useful intervention for boosting model-based control across a range of symptom and trait severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
113
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(133 citation statements)
references
References 47 publications
11
113
1
Order By: Relevance
“…We selected this disorder because the clinical presentation of GAD does not involve compulsive behavior and individual differences in trait anxiety have not been linked to goal-directed planning deficits. 14,17 However, GAD shares a pattern of excessive worry and intrusive thoughts with OCD as well as nonspecific clinical features, such as general distress and impairment. 1 The use of patients with GAD allowed us to assess the potential contribution of these features to goal-directed deficits in OCD, separating compulsivity from obsessionality and general distress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We selected this disorder because the clinical presentation of GAD does not involve compulsive behavior and individual differences in trait anxiety have not been linked to goal-directed planning deficits. 14,17 However, GAD shares a pattern of excessive worry and intrusive thoughts with OCD as well as nonspecific clinical features, such as general distress and impairment. 1 The use of patients with GAD allowed us to assess the potential contribution of these features to goal-directed deficits in OCD, separating compulsivity from obsessionality and general distress.…”
mentioning
confidence: 99%
“…In terms of cognitive flexibility (WCST), the compulsive factor was associated with fewer categories completed (β [SE], −0.57 [0.09]; P < .001) and more nonperseverative errors (β [SE], 5.86 [1.01]; P < .001) and trials to complete the first category (β [SE], 6.32 [1.36]; P < .001). Perseverative errors were not significantly associated with compulsivity (β [SE], 0.87 [0.59]; P = 14)…”
mentioning
confidence: 99%
“…This manipulation demonstrated that model-based control could be boosted within the individual. Moreover, recent work using the same task showed model-based deficits could be improved across a range of transdiagnostic symptoms and traits of psychopathology (Patzelt et al, 2019a). This suggests that incentives might also boost model-based control in aging adults and lead to more flexible decision-making strategies.…”
Section: Model-based Control Across the Lifespanmentioning
confidence: 94%
“…This is why recent research has focused on methods to boost model-based control within the individual. Efforts to increase model-based control using incentives have been successful (Kool, Gershman, & Cushman, 4 2017), and this is also true for people with elevated symptoms and traits of psychopathology (Patzelt, Kool, Millner, & Gershman, 2019a). These findings demonstrate the possibility of boosting model-based control in older adults.…”
Section: Introductionmentioning
confidence: 92%
“…Using this method, we previously showed that a transdiagnostic compulsive dimension maps onto deficits in goal-directed control better than OCD symptoms (Gillan et al, 2016); a finding that has since been replicated (Patzelt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%